INFLUENCE OF HETEROGENEOUS LITHOSPHERIC STRUCTURE ON CONTINENTAL RIFTING: POSSIBLE IMPLICATIONS FOR THE LIGURE-PIEMONTESE OCEAN - Bonini, Marco; Corti, Giacomo; Del Ventisette, Chiara; Principi, Gianfranco; Sani, Federico (Ofioliti, 2004)
Continental rifting represents the thermo-mechanical process by which continents break. This process is characterised by an high variability in terms of duration, volcanicity, width and symmetry. Models formulated to explain such a structural variability consider differences in (e.g., Davison, 1997; Ziegler and Cloetingh, 2004): initial rheological or thermal structure of the lithosphere, rift kinematics (e.g., oblique vs. orthogonal) and mechanics (e.g., pure vs. simple shear), strain rate, melt volumes, presence of pre-existing weakness zones. Among these processes, the lithospheric structure inherited from previous deformation phases and the presence of weakness zones have been shown to play a major role in controlling continental extension (e.g., Dunbar and Sawyer, 1989; Ziegler and Cloetingh, 2004). As a consequence, rifting processes often affect continental lithospheres characterized by important lateral variations in rheology and these variations are able to influence parameters as the width and symmetry of the rift, the patterns of uplift and subsidence, the location and amount of volcanic products. Extension in the Ligure-Piemontese ocean has been shown to be superimposed onto a previous ercinic chain, thus configuring a lithospheric weakness zone. In this frame, lateral rheological heterogeneities is expected to have played a major role in controlling the structure of the passive margins of the Adria/Europe system. In this work, this influence is investigated through scaled analogue modelling. Small-scale experiments were performed in an artificial gravity field of 31g, by using the Large Capacity Centrifuge of the Tectonic Modelling Lab of the CNR-IGG, settled at the Earth-Science Department of Florence University. The models, with dimensions of 10cm x 16cm x 4cm, were built with suitable analogue materials (sand, silicone, oleic acid) able to reproduce the brittle/ductile stratification of the continental lithosphere and were properly scaled to be directly comparable to natural prototypes. The experimental series investigated the occurrence of three different continental lithospheres: 1) a weak orogenic lithosphere (WL; Thickness: 80-100km; Thermo-mechanic Age: 50 Ma; Effective Elastic Thickness: 20km); 2) a normal 4-layer lithosphere (NL; Th: 120km; TA: 250 Ma; EET: 40km); 3) a strong cratonic lithosphere (CL; Th: 140km; TA: 400 Ma; EET: 70km). Results show that in the simple case of WL, continental extension is taken up by regularly-spaced faulting in the upper brittle layer coupled to flow of the ductile lower crust and uppermost lithospheric mantle. No strain localisation configures with this initial rheological stratification; instead, the deformation style can be ascribed to a wide-rifting mode (e.g., Buck, 1991; Brun, 1999). The base of the lithosphere in these models was rather flat, suggesting that no major asthenospheric upraising took place during deformation. In case of lateral variation between WL and CL, deformation was mostly localised at the craton border and within the weak domain; no deformation developed within the strong lithosphere. The largest normal fault developed at the contact between WL and CL, whereas regularly-spaced faults and lower crustal flow (with development of core complex structures) characterised the weakest portion of the models. Extension was accommodated by downward flexure of the WL and elastic rebound with strong shoulder uplift of CL; limited asthenospheric upraising was mainly localised within the WL. In models with NL and CL separated by a central WL, extensional deformation was strongly localised by the weakness zone. This rheological configuration leaded indeed to a rapid necking of the lithosphere and asthenospheric upraising leading to continental break-up in the central part of model. The modelling results support an important role played by the initial lithospheric structure on rift structure and duration and suggest that lateral rheological variations may have an important influence in controlling the local pattern of uplift/subsidence and faulting in continental rift settings. These results may have also relevance for the opening of the Ligure-Pemontese ocean. Preliminarily, the structural conditions of continental extension between the European and Adriatic margin may be correlated to the experiment reproducing the strength contrast between weak and cratonic lithospheres. In particular, the downward flexure associated with low subsidence rates of the WL may well account for the development of the Calcare Massiccio fm. on the Adriatic margin, whereas the areas characterised by high subsidence at the WL-CL contact may be correlated with the coeval development of the Briançonnaise domain in the European margin.